Upaya Peningkatan Hasil Belajar Pai Tentang Shalat Dengan Metode Demonstrasi Melalui Bimbingan Teknis Bagi Siswa Kelas III SDN 004 Rambah Samo Tahun Pelajaran 2016/2017 - Masdiam Masdiam (STKIP Rokania Pasir Pangaraian, 2018)
This research is action research which consists of planning, implementation, observation and reflection. This study consists of two cycles consisting of two meetings in each cycle. This study aims to determine how far the influence of the use of methods of demonstration through technical guidance can improve learning outcomes PAI about prayer for students class III SD Negeri 004 Rambah Samo 2016/2017 school year. The focus of this study is learning by using demonstration methods through technical guidance to raising the results of learning PAI grade III SD Negeri 004 Rambah Samo. From result of analysis got that student learning achievement have improvement of minimum mastery criterion In cycle 1 first meeting average score 64,38 students with completeness 41%. At the second meeting the average score of 70.00 students with 59% mastery. In the first 2 cycles of the first meeting the average score of 76.25 students with 72% completeness. At the second meeting the average score of 88.13 students with 94% complete